2009
DOI: 10.1038/nn.2290
|View full text |Cite|
|
Sign up to set email alerts
|

A dual leucine kinase–dependent axon self-destruction program promotes Wallerian degeneration

Abstract: Axon degeneration underlies many common neurological disorders, but the signaling pathways that orchestrate axon degeneration are unknown. We demonstrate that the dual leucine kinase (DLK) promotes degeneration of severed axons in Drosophila and mice, and its target JNK promotes degeneration locally in axons as they commit to degenerate. This pathway also promotes degeneration after chemotherapy exposure, and thus may be a component of a general axon self-destruction program.Axons degenerate in a range of neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

23
330
6
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 284 publications
(361 citation statements)
references
References 15 publications
23
330
6
2
Order By: Relevance
“…This represents a departure from previous studies that have demonstrated neuroprotective phenotypes resulting from DLK deletion, all of which are dependent on insults that originate in the axon (Chen et al, 2008;Miller et al, 2009;Ghosh et al, 2011;Shin et al, 2012). The divergent DLK localization and function described here argues that DLK may regulate neuronal degeneration in contexts such as cerebral ischemia, where excitotoxicity is a predominant driver of neuronal cell death.…”
Section: Discussioncontrasting
confidence: 74%
“…This represents a departure from previous studies that have demonstrated neuroprotective phenotypes resulting from DLK deletion, all of which are dependent on insults that originate in the axon (Chen et al, 2008;Miller et al, 2009;Ghosh et al, 2011;Shin et al, 2012). The divergent DLK localization and function described here argues that DLK may regulate neuronal degeneration in contexts such as cerebral ischemia, where excitotoxicity is a predominant driver of neuronal cell death.…”
Section: Discussioncontrasting
confidence: 74%
“…Moreover we demonstrate, using a conditional knockout approach, that inhibition of DLK signaling can promote RGC survival in vivo and identify a small molecule kinase inhibitor that protects RGC somata and axons in a rodent model of glaucoma. Our findings, which implicate DLK as being an important player in pathologic neuronal cell death, fit in well with the growing literature demonstrating DLK's role as a key signaling molecule in synapse formation, neuronal development, axonal injury and regeneration, and developmental neuronal degeneration (16)(17)(18)(19)(20)(21)(22)(23).…”
supporting
confidence: 88%
“…DLK has been shown to mediate developmental apoptosis in peripheral motor and sensory neurons (17,18). In adult peripheral neurons, it has been implicated as an important mediator of distal axonal degeneration (22) and proximal axonal regeneration (16,19,20) after axonal injury. It is required for the retrograde transmission of injury mediators such as the JNK scaffold protein JNK interacting protein 3 (JIP3) and phosphorylated STAT3 and plays a role in the induction of expression of proregenerative genes (21).…”
Section: Discussionmentioning
confidence: 99%
“…DLK protein is present in axons, and protein levels are increased in response to axonal injury (5). Loss of DLK has been shown to protect distal axons from Wallerian degeneration (6) and to abrogate stress-induced retrograde c-Jun N-terminal kinase (JNK) signaling through interaction with the scaffolding protein JNK-interacting protein 3 (JIP3) (7)(8)(9). In many instances, injury-induced JNK activation in neurons results in apoptosis through phosphorylation of activator protein 1 (AP-1) transcription factors such as c-Jun, which initiates a proapoptotic gene expression program (10,11).…”
mentioning
confidence: 99%